Physico-Chemical and Mineralogical Characterization of Analavory, Bemololo and Miandrivazo Clays - Elidon, Ramahandry Jean; Baholy, Robijaona Rahelivololoniaina; Andrianirina, Randriantsimbazafy; Wega, Razafindramanga Athou; Rokiman, Letsara; Riana, Razafindrakoto Fanoina Ny; Ngbolua, Koto-te-Nyiwa; Aurelien, Mandimbiiharison (Budapest International Research and Critics University, 2024)
The general objective of this study is to thoroughly characterize the clays of Analavory, Bemololo and Miandrivazo from a physico-chemical and mineralogical point of view. To this end, analyses were carried out on all nine samples. The results provided information on important clay parameters such as moisture content, density, pH, constituent chemical elements and specific surface area, and enabled the clays to be classified according to their clay qualities and plasticity.